Quality green lean energy leadership management practices in Malaysian automotive companies / Argustina Zainuddin...[et al.] - Zainuddin, Argustina; Kuzaiman, Nur Asiah; Mohd Salleh, Noor Azlina; Kasolang, Salmiah (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
Quality Green Lean Energy Leadership Management System is a combination of Green Management System (EMS), Total Quality Management System (TQM) and Lean Manufacturing (LM) with the Energy Management System (EnMS) policy. Therefore, a survey questionnaire was developed and distributed to 30 highly active and recommended automotive vendors in Malaysia by Malaysian Automotive Institute (MAI) and the data was analyzed by using Statistical Package for the Social Sciences (SPSS) v.19. From the survey, it was found that most vendors have been practicing TQM, LM and EMS due to customer requirement, however, there are only a few vendors that are aware of Energy Management System (EnMS). However, from the survey the awareness of the EnMS is still lacking due to lack of action and commitment. In order to turn out with a system model, the implementation practices were separated into 4 classifications which are Foundation Level, Level 1, Level 2 and Level 3. The level of the practices is arranged based on the implementation level. The objective of this system is to achieve customer satisfaction, green management system and energy safety and efficiency,so that the organization can compete in the market.